Sanggit Lakon Carangan: Semiotic Analysis of Bagong Figures in the Ki Seno Nugroho Puppet Show - Widagdo, Sungging; Hadi Purnomo, Sucipto; Supriyanto, Teguh; Balighah Nur Fitriyati , Hikmatun (Sutasoma : Jurnal Sastra Jawa, 2025)
Wayang kulit rose and became the prima donna through the play of the character Bagong by Ki Seno Nugroho on social media. This article aims to analyze the role and meaning of Bagong in the play of wayang kulit by Ki Seno Nugroho through a semiotic approach. Ki Seno Nugroho can bring the character of Bagong to life, not only playing a comedic role but also voicing social criticism and the values of people's wisdom. Roland Barthes' semiotic analysis method examines data in the form of signs and meanings formed in dialogues, gestures, expressions, and scenes involving Bagong. This method consists of two levels, namely denotation (literal meaning) and connotation (cultural and ideological meaning). The semiotic approach was chosen because of its relevance in unraveling the layers of meaning of a cultural text to reveal deeper cultural and ideological implications as well. The data source was taken from the video documentation of Ki Seno Nugroho's performance on the Dalang Seno YouTube channel with the plays Bagong Ratu and Semar Mbangun Kayangan. The results of the analysis show that (1) Bagong plays a role as a representation of the common people, (2) Bagong serves as a medium of symbolic resistance to social inequality, and (3) Bagong serves as a communicative and entertaining conveyor of local wisdom. This study confirms the position of Punakawan as an important narrative device in the play of Javanese puppetry.